2002
DOI: 10.1046/j.1365-3024.2002.00457.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal distribution of distinct mast cell phenotypes during intestinal schistosomiasis in mice

Abstract: Mastocytosis is a common feature of helminth infection in most host species. We examined the temporal distribution and phenotype of mast cells during intestinal schistosomiasis in mice, using antibodies directed against histamine, a general mast cell marker, against mouse mast cell protease-1 (MMCP-1), a mucosal mast cell (MMC) marker, and against tryptase, a predominantly connective tissue mast cell (CTMC) marker. Ileal paraffin and/or cryosections of control, 8- and 15-week-infected mice were quantitatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 30 publications
5
21
0
2
Order By: Relevance
“…These observations were similar to those previously described De Jonge et al 2002;Van Nassauw et al 2001).…”
Section: Histologysupporting
confidence: 92%
See 3 more Smart Citations
“…These observations were similar to those previously described De Jonge et al 2002;Van Nassauw et al 2001).…”
Section: Histologysupporting
confidence: 92%
“…In the intestine, mast cells and sensory nerve fibers are the main components of the neuroimmune interaction, forming an axon reflex pathway which is involved in tissue defense against injury and noxious stimuli (Bienenstock et al 1989a(Bienenstock et al , b, 2001Williams et al 1995Williams et al , 1997. In our experimental model, we observed not only an upregulation of the number of CGRP-ir nerves in the lamina propria of the villi, but also an upregulation of mMCP-I-ir mucosal mast cells in the mucosa of infected animals (De Jonge et al 2002). Double immunostaining (detecting mMCP-I and CGRP) revealed that many of these mucosal mast cells were in close apposition to dense CGRP-ir nerve fibers, which clearly increased in density during the acute and chronic phases of infection.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Mast cells are located in the gut mucosa and submucosa to function in intestinal peristalsis, inflammatory process and related immune responses [19][20][21]. Many studies involving food allergies suggest that mast cells are prominent in the development of IgE-mediated hypersensitivity through an excessive release of large amounts of inflammatory factors, including histamine and some cytokines after activation and degranulation [22].…”
Section: Introductionmentioning
confidence: 99%